Product valuation methods: empirical study on industrial SME - Machado, M. J. C. V. (International Business Management, 2016)
The objectives of the present study are: to analyse whether there is a link between what the theory considers adequate product valuation methods and the opinion of the people in charge of management accounting in companies; to identify factors that explain why the same method is considered adequate in some companies and in others not. We interviewed the people in charge of management accounting in 58 small and medium size Portuguese industrial enterprises. This study gives a contribution for the knowledge on management accounting in two ways. In the first place its results allow the conclusion that there is no link between what the theory and the people in charge of management accounting consider as adequate product valuation methods. Secondly, the results obtained fill in a gap in knowledge because the empirical data show the existence of a new variable influencing what those in charge of management accounting consider to be adequate product valuation methods: the way by which those methods were conceived.